Beyond Digital Transformation: Strategic Trade-Offs Between Technology and Operational Advantage In Indonesia’s Advertising Sector - Harmina Harmina; Yuyun Karystin Meilisa Suade; St Salmah Sharon (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study explores how resource-constrained small and medium-sized enterprises (SMEs) in Indonesia’s advertising sector adapt digital transformation strategies to achieve sustainable development. Using the case of Roxy Maharewa, an SME in Makassar–Gowa, the research examines strategic trade-offs between investing in advanced digital platforms and operationally transformative physical assets. Guided by the Resource-Based View, Strategic Trade-off Theory, and Contingency Theory, this qualitative case study employs semi-structured interviews with key decision-makers. Findings reveal that prioritizing high-capacity production equipment eliminated structural cost disadvantages from outsourced printing, enabling twice to fourth times potential profit margin gains and strengthening market competitiveness. Rather than adopting a fully digital-first approach, the firm employed a hybrid strategy leveraging low-cost digital tools for internal efficiency while maintaining offline relationship management to align with client preferences and infrastructural realities. This asset-led hybrid model demonstrates how SMEs in emerging markets can integrate selective digital adoption with tangible investments to achieve both rapid returns and long-term sustainability. The paper contributes to the discourse on digital transformation by providing a context-sensitive perspective for policymakers and practitioners, emphasizing that in heterogeneous digital readiness environments, blended strategies can deliver superior economic and social.